Exploration of the core protein network under endometriosis symptomatology using a computational approach - El Idrissi, Fatima; Fruchart, Mathilde; Belarbi, Karim; Lamer, Antoine; Dubois-Deruy, Emilie; Lemdani, Mohamed; N’Guessan, Assi L.; Guinhouya, Benjamin C.; Zitouni, Djamel (Frontiers in Endocrinology, 2022)
Background: Approximately 6% to 10% of women of reproductive age worldwide and 2.5% of postmenopausal women are affected by endometriosis. The diagnosis of the disease occurs generally very late due to difficulties in grasping earliest signs of the disorder and its highly complex biological background. Identification of key proteins and biological pathways that may harbor the symptomatology of endometriosis may be helpful in anticipating the diagnosis of endometriosis. Methods: A text mining approach was used by exploring bioinformatics databases. Biological pathway and gene ontology (GO) enrichment analyses were performed using Reactome and GeneCodis, respectively. No direct human participants were required for this study. Existing bioinformatics databases were used for analyses. Protein–protein interaction (PPI) network was constructed by STRING and subsequently the proteins were filtered by degree and betweenness. Results: Three hundreds and nine proteins associated with endometriosis symptomatology from the scientific literature were extracted. Thirty-five key proteins have been selected on the basis of degree and betweenness. The most enriched biological pathways associated with these symptoms were (i) Interleukin-4 and Interleukin-13 signaling (p = 1.11e-16), (ii) Signaling by Interleukins (p = 1.11e-16), (iii) Cytokine signaling in Immune system (p = 1.11e-16), and (iv) Interleukin-10 signaling (p = 5.66e-15). Conclusion: Our findings indicate that both pro- and anti-inflammatory biological pathways may play important roles in the symptomatology of endometriosis. The current data can be used to guide clinical and public health strategies towards the prevention and pre-diagnosis of endometriosis in women of reproductive age.